Correlation Between Nutritional Status, Balance, and Triple Jump Learning Outcomes Among Senior High School Students at Budi Agung Medan - Br Siringo Ringo, Devi Hot Ida Ulina; Waruwu, Romanus; Waruwu, Guswaldi Harapan; Daeli, Pius Populer Putra; Siregar, Primayadi Perwira (Journal of Foundational Learning and Child Development, 2025)
Purpose of the study: This study aimed to investigate the correlation between nutritional status, balance ability, and learning outcomes in triple jump performance among senior high school students at Budi Agung Medan, Indonesia. Materials and methods: A cross-sectional study was conducted with 120 students (60 males, 60 females) aged 16-18 years. Nutritional status was assessed using Body Mass Index (BMI) and body composition analysis. Balance was evaluated using the Stork Balance Stand Test and Y-Balance Test. Triple jump performance was measured through standardized technique assessment and distance achievement. Data were analyzed using Pearson correlation and multiple regression analysis with SPSS v27. Results: Significant positive correlations were found between nutritional status and triple jump performance (r = 0.624, p < 0.001), balance ability and triple jump performance (r = 0.712, p < 0.001), and nutritional status and balance ability (r = 0.543, p < 0.001). Multiple regression analysis revealed that balance ability (β = 0.465, p < 0.001) and nutritional status (β = 0.287, p < 0.01) jointly explained 58.7% of the variance in triple jump learning outcomes. Conclusions: Nutritional status and balance ability are significant predictors of triple jump learning outcomes in adolescents. Physical education programs should incorporate nutritional education and balance training to optimize athletic performance development.